The legacy of colonial fire management policies on traditional livelihoods and ecological sustainability in savannas: Impacts, consequences, new directions. (15th February 2019) - Moura, Livia C.; Scariot, Aldicir O.; Schmidt, Isabel B.; Beatty, Robin; Russell-Smith, Jeremy
Abstract: Land occupation and management systems have defined fire regimes and landscapes for millennia. The savanna biome is responsible for 86% of all fire events, contributes to 10% of the total carbon emissions annually and is home to 10% of the human population. European colonization has been associated with the implementation of fire suppression policies in many tropical savanna regions, markedly disrupting traditional fire management practices and transforming ecosystems. In this paper we assess savanna burning approaches from pre-colonial to contemporary eras in three regions: northern Australia, southern Africa and Brazil. In these regions, fire suppression policies have led to (i) conflicts between government authorities and local communities; (ii) frequent late dry season wildfires and/or (iii) woody encroachment. Such consequences are facilitating changes to fire management policies, including recognition and incorporation of traditional ecological knowledge in contemporary community-based adaptive savanna fire management. Such programs include implementation of prescribed early dry season fires and, in some regions, generating income opportunities for rural and traditional communities through the reduction of late dry season wildfires and associated greenhouse gas emissions. We present a brief history of fire management policies in these three important savanna regions, and identify ongoing challenges for implementation of culturally and ecologically sustainable fire management policies. Highlights: Many tropical savanna regions have been subjected to fire suppression policies. Fire prohibitions caused conflicts, wildfires and cultural and livelihood impacts. Contemporary fire policies concern traditional systems, environment and livelihood. Effective fire policies address adaptive, inclusive and integrative management.